Mathematical representation ability of VIII grade students in linear equation using math literacy-based E-module - Firly Agrisa; Zuli Nuraeni; Novita Sari (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2025)
This study aims to describe mathematical representation ability of 8th grade students in learning linear equation using mathematical literacy-based e-module. This research is a descriptive research with a quantitative approach. This research was conducted on VIII.4 grade students of SMP Negeri 45 Palembang with 29 students in total. Data was collected using written tests and interviews. Based on mathematical representation ability test results, students abilities are as follows: 13.79% of high-ability students, 68.96% of medium-ability students and 17.24% of low-ability students. The mathematical representation ability of students after learning using e-module is in low category with 55,17 as average score.